PENGARUH KARAKTERISTIK PEKERJAAN, KOMPETENSI, DAN LINGKUNGAN PEKERJAAN TERHADAP KINERJA PEGAWAI PADA BIRO KESRA PROVINSI JAWA BARAT - Asep Achjar Adimihardja; Barkah Rosadi Achjar Adimihardja (Halu Oleo University, 2023)
In every organization, the performance shown by employees is a determining factor for the success of the organization. This study aims to identify the determinants of employee performance, by looking at the role of job characteristics, employee competence, and work environment. This study uses a quantitative approach with a survey as a data collection tool. The population of this study were employees of the Welfare Bureau of West Java Province, with a total of 76 respondents. The data obtained were analyzed by multiple regression analysis through SPSS software. The results of this study indicate that the performance of employees of the Welfare Bureau of West Java Province is influenced by job characteristics, employee competence, and their work environment. This research can be input for decision makers in the Welfare Bureau of West Java Province to consider factors that can improve employee performance